A influência dos hiperlinks na leitura de hipertexto enciclopédico digital - Ilza Maria Tavares Gualberto (2008)
This work aimed at observing the influence of hyperlinks in the construction of meaning in the reading of digital encyclopedic hypertext. My starting point was the assumption that the characteristics of the linguistic terms materialized in hyperlinks could instigate or inhibit the hyper-reader´s navigation. I took into account that these characteristics were determined by stronger vital relations or tenuous relations between the hyperlink and the generic space activated by a material anchor thatrepresented the theme. I assumed the hypothesis that since the hyper-reader accesses certain hyperlinks, mental spaces are built producing emergent structures, whose meanings are possible through the establishment of vital relations. I used as theoretical support Fauconnier´s Theory of Mental Spaces (1994, 1997) and Fauconnier and Turner´s Theory of Conceptual Blending (2002). The corpus of thisresearch consisted of texts produced for a pamphlet, answers to some questions on the subject of hyperlinks, interviews and direct observations that were computed from tables during the execution of the tasks. I used three versions of the same hypertext, adapted from Wikipedia. In the first version, both the hyperlinks that refer to the textual block and the block itself are materialized by linguistic expressions that establish vital relations to the generic space. In the second version, the hyperlinksare materialized by linguistic expressions that establish tenuous relations to the generic space, but the textual block to which these hyperlinks refer maintains a strong vital relation to the generic space. In the third version, both the textual hyperlinks and the block to which they refer are materialized by linguistic expressions that establish tenuous relations to the generic space. This methodological procedure allowed me to see that the mere access to the hyperlink and, consequently, to thetextual block, is not a guarantee that mental spaces are constructed and compressed into new meanings. Another interesting point concerns to the execution of the proposed tasks, as in the pamphlet production, the number of accesses and meanings built from the textual block provided by the hyperlink was lower than the same procedure in the task of answering questions, which instigated, directed and in some way required the access and the construction of meanings. However, when the readers came across textual blocks whose meanings did not establish relations to the generic space activated, such meanings were dropped, leading the hyper-reader to use information from its own repertoire of knowledge. It was also noted that the number of accesses to the hyperlinks decreased due to the fact that the hyperlink does not meet the hyper-reader´s expectations. This research leads us to concludethat, although it is essential that the language terms materialized in hyperlinks establish strong vital relations to the generic space activated by material anchors, it is also required the existence of vital relations from the textual block to which the hyperlink refers to the generic space that is activated, because only from these vital relations it will be possible that conceptual blending can occur and that the meaning can emerge.